Maintaining the Integrity and Authenticity of Medical Images Using Integer Wavelet Transform and Practical Swarm Optimisation Technique - Dr. Mansour Ahwidy Khamis (African Journal of Advanced Pure and Applied Sciences, 2025)
Significant advances in health care technology, especially in medical imaging, have profoundly altered the field. Digital tools such as radiography, telemedicine, and Picture Archiving and Communication Systems (PACS) have heightened the need for robust image security measures. Medical image security attempts to safeguard the accuracy and legitimacy of pictures. Integrity entails avoiding the possibility of tampering, whereas authenticity verifies the authenticity of images. The absence of these can lead to inaccurate diagnoses and inappropriate treatments. The primary objective of the work is to explore the efficacy and benefits of the Integer Wavelet Transform (IWT) and the Practical Swarm Optimisation (PSO) technique for protecting the integrity and authenticity of digital medical images. The research has two key aims. Firstly, it investigates the effectiveness of PSO-determined IWT coefficients in digital image watermarking. Secondly, it illustrates the authentication scenario using medical images, incorporating patient data and encrypted input into watermarking schemes. A normalised correlation coefficient (NCC) quantifies the similarity in recovered images, serving as the objective function in (PSO). The experimental results in the form of the time-frequency representation of the decomposed image using the IWT allow the visibility of the integrity signature on the original medical image. The proposed watermarking technique based on the integer wavelet transform and practical swarm optimisation scheme can provide a robust watermarking technique in the top two frequency bands and maintain the fidelity of the original image.